Conceptual framework of service learning in technical and vocational education at the Nigerian tertiary education - Deba, Ahmad Aliyu (2015)
Current experiential learning approach in the Nigerian Technical and Vocational education (TVE) has been criticized for not meeting the desired challenges. The TVE departments give less emphasis to service learning due to lack of conceptual framework that can guide its implementation. Hence, this research aimed to develop a conceptual framework of service learning in TVE for Nigerian tertiary education. The research was designed to determine the aspects and their respective areas for the development of a conceptual framework for effective service learning in TVE. Mixed methods sequential explanatory research design was employed for this research. Two hundred and sixty seven (267) respondents comprised of 206 lecturers, 45 heads of department and 16 faculty deans and deputy deans were chosen using stratified random sampling technique from eight TVE departments of 15 tertiary education institutions in the North Eastern Sub-Region of Nigeria. Six service learning experts in TVE were interviewed. A researcher-made structured questionnaire consisting of 67 items and interview protocol on the six major aspects of service learning were used as instruments for the quantitative and qualitative data collection respectively. The instruments were validated by three experts and the reliability of the questionnaire was established through a pilot study. Stepwise linear regression analysis, structural equation modeling (SEM) and confirmatory factor analysis (CFA) were used to analyse the quantitative research questions whereas content analysis was used to analyse the qualitative research question. The findings revealed a conceptual framework of service learning for TVE in the Nigerian tertiary education which include course learning objective, faculty community involvements, students’ learning outcomes, assessment/reflection procedures, community service needs and pedagogical support services which covers a total of sixty seven areas of service learning in TVE. In conclusion, the research recommended for the implementation of the conceptual framework in TVE at the tertiary institutions in Nigeria.